Butyrate Ameliorates Intestinal Epithelial Barrier Injury Via Enhancing Foxp3+ Regulatory T-Cell Function in Severe Acute Pancreatitis Model - Xiao, Shen; Jing, Sun; Jiakui, Sun; Lei, Zou; Ying, Liu; Han, Liu; Xinwei, Mu; Weiqin, Li (Turkish Journal of Gastroenterology, 2022)
Background: This study aimed to examine the effect of sodium butyrate on severe acute pancreatitis-related gut barrier injury in a rat model and explore its mechanism. Methods: Male rats randomly fell into 3 groups, that is, the control, the severe acute pancreatitis group, and the severe acute pancreatitis+butyrate group. Rats in the control group received sham operation, while rats in the severe acute pancreatitis group and severe acute pancreatitis+butyrate group received severe acute pancreatitis induction by intraductal infusion of 4% sodium taurocholate. After that, rats in the severe acute pancreatitis+butyrate group were fed with sodium butyrate solution with free access. Intestinal barrier injury was measured based on the expression of tight junction proteins by reverse transcription polymerase chain reaction, Western blotting assay as well as immunohistochemical staining. The variation of Treg cells was measured by reverse transcription polymerase chain reaction, Western blotting assay, immunohistochemical staining, and flow cytometry analysis. Results: Compared to rats in the control, rats in the severe acute pancreatitis group showed significantly higher pathohistological scores (P < .001) in the intestine, as well as decreased expression of occludin and ZO-1. While, rats in the severe acute pancreatitis+butyrate group showed mitigated histologic lesions (P < .05) and increased expressions of occludin and ZO-1. In addition, rats in the severe acute pancreatitis group showed the obvious reduction in the expressions of Foxp3 and GPR109a and the decreased percentage of Treg cells in the intestine (P < .001) compared to rats in the control. However, rats in the severe acute pancreatitis+butyrate group showed markedly increased expressions of Foxp3 and GPR109a and the upregulated percentage of Treg cells (P < .01). Conclusion: Butyrate could significantly mitigate the intestinal injury induced by severe acute pancreatitis, probably by inducing the differentiation of Treg cells. Cite this article as: Xiao S, Jing S, Jiakui S, et al. Butyrate ameliorates intestinal epithelial barrier injury via enhancing Foxp3+ regulatory T-cell function in severe acute pancreatitis model. Turk J Gastroenterol. 2022;33(8):710-719.